1970
DOI: 10.25081/rrst.2019.11.6082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of precipitation datas by Mann Kendall and Sperman's Rho rank correlation statistical approaches in Nevsehir Province of Turkey

Abstract: In this research, the total and maximum precipitation values of long years (1970-2019) of Nevşehir province, Ürgüp districts and 34 years of Avanos 1986-2019 were subjected to the Mann Kendall and Sperman's Rho rank correlation tests. In this study; Change trends of the precipitation are presented with graphic distrubitions. According to the results of the trend analysis, it has been observed that the average maximum precipitation value for long years in Avanos district, Nevsehir Province and Ürgüp district is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Looking at the literature, we see that Spearman's Rho and Kendall correlation tests are frequently used for the evaluation of climate parameters. Evaluation of climate parameters with such correlation tests will result in high accuracy of climate forecasts [83][84][85][86].…”
Section: Resultsmentioning
confidence: 99%
“…Looking at the literature, we see that Spearman's Rho and Kendall correlation tests are frequently used for the evaluation of climate parameters. Evaluation of climate parameters with such correlation tests will result in high accuracy of climate forecasts [83][84][85][86].…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted with 50 years of data covering the years 1986-2019 in Nevşehir, it was seen that the annual average precipitation amount was 362.9 mm. Total precipitation is 130.3 mm in spring, 123.5 mm in winter, 71.6 mm in autumn and 37.5 mm in summer [5].…”
Section: Methodsmentioning
confidence: 99%
“…Nevşehir, which has a warm and temperate climate; It receives much more precipitation in winter than in summer. The annual average temperature of Nevşehir province is 10.73 • C, and the average precipitation is 362.9 mm Bağdatlı and Can (2019); Bağdatlı and Arıkan (2020). In a study conducted on the climate data observed in Nevşehir province for many years (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019), the maximum open surface evaporation for many years in Nevşehir Center was calculated as 59.7 mm, and the total open surface evaporation was 1017.6 mm Bağdatlı and Ballı (2019).…”
Section: Methodsmentioning
confidence: 99%